The way of the househusband. 1 - Ōno, Kōsuke (VIZ MEDIA, 2019)
"He was the fiercest member of the yakuza, a man who left countless underworld legends in his wake. They called him 'the Immortal Dragon'. But one day he walked away from it all to walk another path--the path of the househusband! The curtain rises on this cozy yakuza comedy!"--Provided by publisher.